2020
DOI: 10.1101/2020.08.05.238071
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Paradoxical relationships between active transport and global protein distributions in neurons

Abstract: Neural function depends on continual synthesis and targeted trafficking of intracellular components, including ion channel proteins. The detailed biophysics active ion channel transport are increasingly well understood, along with the steady-state distribution of functional channels in the membrane. However we lack a quantitative understanding of how transport mechanisms give rise to stable expression patterns, and how live measurements of active transport relate to static estimates of channel density in neuri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
(61 reference statements)
0
1
0
Order By: Relevance
“…In a more general context, Bauer et al showed that the molecules of Rgs4 (regulator of G protein signaling 4) mRNA patrolled dendrites to transiently interact with multiple synapses, in agreement with the sushi-belt model [88,89]. Moreover, the authors observed that the majority of RNA-transporting granules showed bidirectional transport in dendrites independently of 3′-UTR, but Rgs4 3′-UTR caused an anterograde transport bias requiring the Staufen 2 protein.…”
Section: Arc Mrna Trafficking Within Neuronsmentioning
confidence: 77%
“…In a more general context, Bauer et al showed that the molecules of Rgs4 (regulator of G protein signaling 4) mRNA patrolled dendrites to transiently interact with multiple synapses, in agreement with the sushi-belt model [88,89]. Moreover, the authors observed that the majority of RNA-transporting granules showed bidirectional transport in dendrites independently of 3′-UTR, but Rgs4 3′-UTR caused an anterograde transport bias requiring the Staufen 2 protein.…”
Section: Arc Mrna Trafficking Within Neuronsmentioning
confidence: 77%